2016
DOI: 10.3847/0004-6256/152/1/17
|View full text |Cite
|
Sign up to set email alerts
|

RAPID EVOLUTION OF GSC 03144-595, a NEW TRIPLE-MODE RADIALLY PULSATING HIGH-AMPLITUDE Δ SCUTI

Abstract: We present the results of a multi-year study of the high-amplitude δ Scuti (HADS) star GSC 03144-595. The star was observed between June and September in 2011 and 2014 for 13 nights and 28 nights, respectively. Based on our results, we argue that GSC 03144-595 is a new triple-mode radially pulsating HADS, only the fifth discovered and only the second that has a fundamental frequency in the traditional δ Scuti regime. While the frequencies and amplitudes of the fundamental and first harmonic were found to be un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The results of the seismic models re-confirm the conclusion that f 0 , f 1 , and f 2 are the fundamental, first overtone, and second overtone radial p-modes, respectively [11]. Moreover, it shows that this star locates in the later evolutionary phase of the Hertzsprung gap, which is a more rapidly evolving phase compared with those stars in the earlier evolutionary phase of the Hertzsprung gap (such as AE UMa [5] and VX Hya [6]).…”
Section: Main Bodysupporting
confidence: 71%
See 1 more Smart Citation
“…The results of the seismic models re-confirm the conclusion that f 0 , f 1 , and f 2 are the fundamental, first overtone, and second overtone radial p-modes, respectively [11]. Moreover, it shows that this star locates in the later evolutionary phase of the Hertzsprung gap, which is a more rapidly evolving phase compared with those stars in the earlier evolutionary phase of the Hertzsprung gap (such as AE UMa [5] and VX Hya [6]).…”
Section: Main Bodysupporting
confidence: 71%
“…KIC6382916 (J19480292+4146558, also known as GSC 03144-595) is a HADS to be monitored extensively by the Kepler space telescope for its pulsation properties, which shows three independent frequencies (pulsation modes) in its light curves [10]. These three pulsation modes have been confirmed as the fundamental, the first overtone and the second overtone radial p-modes [11], and T eff = 6950 ± 100 K, log g = 3.7 ± 0.1 and v sin i = 50 ± 10 km s −1 have been estimated by the high-dispersion spectra [10]. [6,12,13], the variations of the frequencies can be derived from the variations of the phases.…”
Section: Main Bodymentioning
confidence: 99%
“…KIC6382916 (J19480292+4146558, also known as GSC 03144-595) is a HADS to be monitored extensively by the Kepler space telescope for its pulsation properties, which shows three independent frequencies (pulsation modes) in its light curves (Ulusoy et al 2013). These three pulsation modes have been confirmed as the fundamental, the first overtone and the second overtone radial p-modes (Mow et al 2016), and T eff = 6950 ± 100 K, log g = 3.7 ± 0.1 and v sin i = 50 ± 10 km s −1 have been estimated by the high-dispersion spectra (Ulusoy et al 2013). Using the long-cadence (LC) photometric data of KIC6382916 lasted from BJD 2454953 to 2456424 (Quarter 0-17), we extract the first 23 frequencies with largest amplitudes (which have a cut-off of 1.3 mmag, see in Table 2 for more details) to study the variations and interactions of them.…”
mentioning
confidence: 76%
“…tively (Mow et al 2016). Moreover, it shows that this star locates in the later evolutionary phase of the Hertzsprung gap, which is a more rapidly evolving phase compared with those stars in the earlier evolutionary phase of the Hertzsprung gap (such as AE UMa (Niu et al 2017) and VX Hya (Xue et al 2018)).…”
mentioning
confidence: 99%
“…Only five HADS stars with three consecutive radial modes, i.e. AC And (Fitch & Szeidl 1976), V823 Cas (Jurcsik et al 2006), V829 Aql (Handler et al 1998), GSC 762-110 (Wils et al 2008) and GSC 03144-595 (Mow et al 2016), are found at present.…”
Section: Introductionmentioning
confidence: 90%